Análisis de la recaudación tributaria por SUNAT en la región Loreto por impuesto a la renta, periodo 2016 - 2020 - Ramos Egoavil, Alva Cristal (2022)
Tax collection is an activity of great importance for the State, because through it, SUNAT, in attributions to its functions, collects the financial resources that are generated by the fulfillment of the tax obligations of the taxpayers, and that said resources are needed to finance public spending. The present investigation called "Analysis of Tax Collection by SUNAT in the Loreto region for Income Tax, period 2016 – 2020”, has as a general objective to determine the evolution of tax collection by SUNAT in the Loreto region for Income Tax. Income in the period 2016 to 2020. In addition, the research was of a quantitative type and a non-experimental descriptive design – cross – sectional. Finally, through the analysis and discussion that tax collection presents a negative evolution with respect to the study period.